Survival in amoeba: a major selection pressure on the presence of bacterial copper and zinc resistance determinants?: identification of a "copper pathogenicity island" - Hao, Xiuli; Luthje, Freja L.; Qin, Yanan; McDevitt, Sylvia Franke; Lutay, Nataliya; Hobman, John L.; Asiani, Karishma; Soncini, Fernando C.; German, Nadezhda; Zhang, Siyu; Zhu, Yong-Guan; Rensing, Christopher (Springer, 2015)
The presence of metal resistance determinants in bacteria usually is attributed to geological or anthropogenic metal contamination in different environments or associated with the use of antimicrobial metals in human healthcare or in agriculture. While this is certainly true, we hypothesize that protozoan predation and macrophage killing are also responsible for selection of copper/zinc resistance genes in bacteria. In this review, we outline evidence supporting this hypothesis, as well as highlight the correlation between metal resistance and pathogenicity in bacteria. In addition, we introduce and characterize the "copper pathogenicity island" identified in Escherichia coli and Salmonella strains isolated from copper- and zinc-fed Danish pigs.